Equitable urban green space planning for sustainable cities: a GIS-based analysis of spatial disparities and functional strategies - Sayyed Kifayatullah; Zafeer Saqib; Muhammad Irfan Khan; Muhammad Zaman-ul-Haq; Dmitry E. Kucher; Sajid Ullah; Aqil Tariq (Scientific Reports)
Abstract Urban Green Spaces (UGS) are critical for fostering ecological sustainability and social equity in rapidly urbanizing cities like Islamabad, Pakistan. This study aimed to comprehensively map and classify Islamabad’s UGS, identify spatial disparities, and evaluate their ecological, recreational, and social functions. The research also proposed sustainable strategies for managing UGS to address urban challenges, including climate adaptation, biodiversity loss, and social inequity. The study developed a detailed spatial map of Islamabad’s UGS using Geographic Information Systems (GIS) and high-resolution satellite imagery. Seven typologies were categorized and analyzed, including parks, playgrounds, institutional green spaces, and waterways. Field surveys and random sampling validated the thematic maps, achieving an accuracy rate of 95.68% based on statistical metrics like Kappa coefficients. The study revealed significant disparities in UGS distribution. Wealthier zones had larger, well-maintained green spaces, while denser areas lacked accessible and functional UGS. Recreational spaces, institutional greenery, and waterways played a vital role in enhancing biodiversity, urban aesthetics, and community well-being, though many remain underutilized or degraded. Institutional green spaces contributed significantly to urban sustainability, comprising 17.05 km² of the total UGS area. The research highlights UGS as an essential Nature-Based Solution (NBS) for addressing urban challenges like heat islands, stormwater management, and social inequalities. The findings serve as a model for other rapidly urbanizing cities seeking ecological and social balance.